PGIS Supported Knowledge Based Participation and Evidences of Empowered Community Members - Mulalu, M.; Veenendaal, Bert (-, 2011)
In much of Botswana’s rural population, formal business ethic is not common and the business environment contains fragmented and incomplete information. Under such mainly agrarian economies, the villagers do not know where the customers for their produce are, there is limited technology and often the farmers are not aware of the potential benefits from their agro-businesses. Many people are also not aware of the supportive policy frameworks, the agricultural programs/projects that the government has set up for them and the attendant financial support programs that are intended to implement the programs. The villagers participate more in social welfare programs from which they do not earn enough to live dignified lives. Participation and empowerment paradigms have been used in development programs to foster rural community development. However, many national and international development projects have been implemented with insufficient understanding of participation and empowerment processes. Using participation as learning and empowerment as informed participation within community group interactions, this paper presents the use of participatory action research implemented through participatory geographic information system (PGIS), to facilitate community learning and the construction of a PGIS based knowledge repository. The knowledge repository addressed issues of fragmented and incomplete information and also served more to facilitate knowledge construction, encourage local innovation and forged links with the local community development institutions as well as district and central government institutions.